ESL learners' attitude, motivation and performances in learning English language vocabulary through ESL websites - Shereena Sreetharam, 1983-; Noor Zainab Abdul Razak, supervisor; Fakulti Pendidikan (2010)
Thesis (Sarjana Pendidikan (Pengajaran Bahasa Inggeris sebagai Bahasa Kedua)) - Universiti Teknologi Malaysia, 2010